Implementation of Project-Based Learning in Electrical Engineering Materials to Improve Character Education of Engineering Students - Doni Setiawan; Nina Faoziyah (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to describe the implementation of the Project Based Learning (PjBL) model on Electrical material and its impact on Improving Character Education of Engineering Students. The main project implemented is the creation of a group Electrical Circuit Project. The type of research is Classroom Action Research which was carried out for two cycles with 15 Electrical Engineering and Mechanical Engineering students as subjects. The results of the analysis of assessment, observation, and documentation show that the implementation of Project Based Learning through the electrical circuit creation project is significantly able to increase collaboration, concern, and sharing of tasks among students, which are key indicators of mutual cooperation. This increase is evidenced by the percentage of completion of mutual cooperation attitudes which was originally 40% in the pre-action, increased to 73% in cycle I (Good category), and reached 93% in cycle II (Very Good category). This study concludes that the Project Based Learning model with electrical circuit projects is effective in fostering mutual cooperation attitudes in students.